Macrophages and osteoclasts: similarity and divergence between bone phagocytes - Halper, Julia; Dolfi, Bastien; Ivanov, Stoyan; Madel, Maria-Bernadette; Blin-Wakkach, Claudine (Frontiers in Immunology, 2025)
Both macrophages and osteoclasts are vital immune components of the bone microenvironment. While macrophages play an essential role in phagocytosis, pathogen clearance and tissue remodeling, osteoclasts are well described for their bone resorption capacity. However, osteoclasts are much more than bone resorbing cells. While macrophages have been intensively studied as immune cells, the immune function of osteoclasts has long been neglected until recent evidence demonstrated that they play an important role in modulating immune responses. Both macrophages and osteoclasts exhibit the phenotypic and functional characteristic plasticity of the myeloid lineage, which depends on their origin and environment. Besides their common progenitors, osteoclasts and macrophages share several joint mechanisms ranging from cell fusion and phagocytosis to immune function and tissue remodeling. In this review, we discuss and illustrate the functional and characteristic parallels between macrophages and osteoclasts.